Defective PTEN-induced kinase 1/Parkin mediated mitophagy and neurodegenerative diseases - Braun, Megan M.; Puglielli, Luigi (Frontiers in Cellular Neuroscience, 2022)
The selective degradation of mitochondria through mitophagy is a crucial process for maintaining mitochondrial function and cellular health. Mitophagy is a specialized form of selective autophagy that uses unique machinery to recognize and target damaged mitochondria for mitophagosome- and lysosomes-dependent degradation. This process is particularly important in cells with high metabolic activity like neurons, and the accumulation of defective mitochondria is a common feature among neurodegenerative disorders. Here, we describe essential steps involved in the induction and progression of mitophagy, and then highlight the various mechanisms that specifically contribute to defective mitophagy in highly prevalent neurodegenerative diseases such as Parkinson disease, Alzheimer’s disease, Huntington’s disease, and Amyotrophic Lateral Sclerosis.